Sacred multi-use: Interventions in Barcelona’s religious heritage - Arboix-Alió, Alba (Actas de Arquitectura Religiosa Contemporánea, 2020)
The liturgical renewal approved during the Second Vatican Council meant a morphological transformation for the religious buildings. Some churches that were at that time on project stage were then adapted to the new guidelines. Focusing in Barcelona, two cases stand out: the parish of Sant Sebastià, MBM’s work, and Sant Jeroni, a church included in the Iberian DoCoMoMo. But over the years we realize that the most interesting cases are those in which social change was also satisfied. Thus, centuries-old churches adapt the linear sacred space while at the same time providing perimeter zones for alternative uses. This is the case of Santa Maria del Mar or Santa Anna. This communication will examine the examples cited and will think about this last way of operating. It’s not only a matter of ‘conditioning’ or ‘reuse’, but about ‘multi-use’, a strategy with a vision of future, but already present in the gospels.